Deep sequencing analysis of acute conjunctivitis in Burkina Faso, Africa. Issue 1 (24th January 2022) - Bountogo, Mamadou; Sié, Ali; Coulibaly, Boubacar; Ruder, Kevin; Chen, Cindi; Zhong, Lina; Colby, Emily; Lebas, Elodie; Deiner, Michael; Hinterwirth, Armin; Lietman, Thomas M; Seitzman, Gerami D; et al.
Abstract: Background: Seasonal and epidemic conjunctivitis (pink eye) infections are highly contagious and impose a significant economic burden worldwide. Long-term visual impairment can occur. Methods: This study used metagenomic deep sequencing to evaluate pathogens causing acute infectious conjunctivitis in Burkina Faso. Results: We found that pathogens causing conjunctivitis in Burkina Faso are diverse, with human adenoviruses responsible for a small fraction of the samples tested. Conclusions: These results are unexpected and suggest the importance of regional surveillance.